Застосування формальних моделей та методів у видобуванні та виявленні знань зі сховищ даних - Катренко, С. А.; Буров, Є. В. (Видавництво Національного університету “Львівська політехніка”, 2020)
In this article the formal models and data mining methods are analysed with proposal of models classification. This classification allows use of formal models in the information systems and in the decision support systems design process. These models are useful in case of large data volumes.
Keywords: 681.3